Parthenium hysterophorus and its Management in Crop and Non-crop Environment - Vijayakumar, S.; Saravanane, P.; Khanam, Rubina (Chronicle of Bioresource Management, 2023)
Parthenium hysterophorus, commonly known as Gajar ghas, has exhibited rapid proliferation throughout India, encompassing approximately 35 million hectares of land. Its invasive and aggressive behavior has precipitated a host of health concerns, diminished biodiversity, and negatively impacted agricultural productivity. While the government has launched initiatives to combat its spread, their efficacy remains constrained by the widespread lack of public awareness. The Indian Council of Agricultural Research (ICAR) diligently conducts annual awareness weeks, imparting knowledge about various control strategies to the public. To effectively confront the menace posed by Parthenium hysterophorus, it is imperative to employ comprehensive mass media campaigns, involving collaboration with non-governmental organizations (NGOs) and private entities. These concerted efforts are indispensable in addressing the multifaceted challenges posed by Parthenium hysterophorus and mitigating its adverse effects on human health, biodiversity, ecosystems, and agriculture.